2012
DOI: 10.1179/1743294411y.0000000071
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbon and nitrogen ion implantations on surface and tribological properties of Ti–Al–Si–N coatings

Abstract: The post-treatment of ion implantation on hard coatings attracts a great deal of attention because of the improvement in coating surface properties. The present research investigates the effect of nitrogen (N), carbon (C) and carbon followed with nitrogen (CzN) ion implantations on the structural and mechanical properties of the Ti-Al-Si-N coatings. Ion implantations were performed at an energy of 50 keV and different doses. The surface properties of the implanted layer were identified by a variety of analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…The residual compressive stress of the Ti-DLC coatings as a function of the Ti transition layer thickness t 0 (μm) is presented in Figure 9 . It can be observed that when t 0 increases, the residual compressive stress decreases sharply from 12.4 GPa at 0 μm to 2.4 GPa at 1.1 μm, which serves as evidence that the residual compressive stress causes the G peak shifting upward to a higher wavenumber as in previous Raman studies [ 40 ]. As we know, this strain is produced by different shrinkage tendencies owing to the direct contact between the coating and Al alloy substrate.…”
Section: Resultssupporting
confidence: 72%
“…The residual compressive stress of the Ti-DLC coatings as a function of the Ti transition layer thickness t 0 (μm) is presented in Figure 9 . It can be observed that when t 0 increases, the residual compressive stress decreases sharply from 12.4 GPa at 0 μm to 2.4 GPa at 1.1 μm, which serves as evidence that the residual compressive stress causes the G peak shifting upward to a higher wavenumber as in previous Raman studies [ 40 ]. As we know, this strain is produced by different shrinkage tendencies owing to the direct contact between the coating and Al alloy substrate.…”
Section: Resultssupporting
confidence: 72%
“…Figure 1 shows a typical cross-sectional SEM image of ta-C film. It exhibits that the adhesion strength and hardness of the composite film are favourably improved and hardened by its compact structure 12. Analysis of C, Cr and Si distributions across the film thickness, from the film surface down to the datum surface of the substrate, shows that the elements of C and Cr vary remarkably from layer to layer.…”
Section: Resultsmentioning
confidence: 99%
“…Various approaches have been investigated in order to achieve extended lifetimes, such as controlling the plastic deformation of coatings by grain refinement according to the Hall-Petch effect, 1 work hardening, 2 solid solution strengthening, 3 precipitation hardening, 1 quenching 4 and surface strengthening by nitriding or nitrocarburizing. 5,6 Among them the most prominent relative method is the deposition of superhard transition metal nitride films, either binary such as TiN and CrN [7][8][9][10] or tailored ternary and quaternary systems, 11,12 due to their exceptional combination of properties, such as hardness, electrical conductivity, resistance to oxidation and refractory character. In particular, Reiter et al 10 reported that the addition of Al to the Cr-N structure increases its decomposition temperature because of the strengthening effect of the Al inclusion in the Cr-N bonds.…”
Section: Introductionmentioning
confidence: 99%